1997
DOI: 10.1002/(sici)1097-0355(199723)18:3<274::aid-imhj4>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Facial expressivity to acute pain in cocaine-exposed toddlers

Abstract: Expressive emotion regulation in response to stress following inoculation was examined in 30 18‐month‐olds. Fourteen were exposed to cocaine in utero and 16 were drug‐free. Findings indicated that the cocaine‐exposed group displayed fewer discrete negative expressions of distress and anger and more sadness in response to acute pain. These results suggest that cocaine exposure may exert an influence on the expression of emotion into the second year of life. © 1997 Michigan Association for Infant Mental Health

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
1
10
1
Order By: Relevance
“…In addition to heritable influences, birth mother illicit drug use during pregnancy was negatively associated with child negative reactivity, such that children whose birth mothers used illicit drugs more frequently during pregnancy showed significantly lower levels of negative reactivity compared to their peers. Our findings are consistent with studies that have found low reactivity of prenatally drug-exposed children (Alessandri et al, 1993;Molitor et al, 2003;Roumell et al, 1997). There are, however, studies that have found high reactivity in children whose mothers used drugs while pregnant (Metosky & Vondra, 1995;Richardson, Goldschmidt, & Willford, 2008) which is not consistent with our findings.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In addition to heritable influences, birth mother illicit drug use during pregnancy was negatively associated with child negative reactivity, such that children whose birth mothers used illicit drugs more frequently during pregnancy showed significantly lower levels of negative reactivity compared to their peers. Our findings are consistent with studies that have found low reactivity of prenatally drug-exposed children (Alessandri et al, 1993;Molitor et al, 2003;Roumell et al, 1997). There are, however, studies that have found high reactivity in children whose mothers used drugs while pregnant (Metosky & Vondra, 1995;Richardson, Goldschmidt, & Willford, 2008) which is not consistent with our findings.…”
Section: Discussionsupporting
confidence: 79%
“…Maternal illicit drug use during pregnancy, including cocaine, marijuana, and amphetamine (the most often studied illicit drugs), has been associated with reduced negative emotional reactivity in infants and toddlers (e.g., Alessandri et al, 1993;LaGasse et al, 2011;Molitor, Mayes, & Ward, 2003;Roumell, Wille, Abramson, & Delaney, 1997). For example, 18-monthold toddlers whose mothers used cocaine with or without marijuana, alcohol, and tobacco during pregnancy exhibited lower levels of negative emotions (e.g., anger, distress) after inoculation (Roumell et al, 1997) and showed less negative reactivity during a separation task (Molitor et al, 2003) compared to unexposed children. However, this finding of less reactivity in children whose mothers used illicit drugs while pregnant has not been consistently replicated across studies.…”
Section: Prenatal Influences In Explaining Child Effects On Parental mentioning
confidence: 99%
“…Additionally, effects of drug exposure might be expected for the socialemotional outcome. In contrast to studies that have employed growth or cognitive measures in early childhood, those employing measures related to problems of arousal, affect, or attention regulation in early infancy have been more consistent in finding associations with prenatal cocaine exposure (Alessandri, Sullivan, Imaizumi, & Lewis, 1993;Bard, Coles, Platzman, & Lynch, 2000;Coles, Bard, Platzman, & Lynch, 1999;Mayes, Bornstein, Chawarska, Haynes, & Granger, 1996;Roumell, Wille, Abramson, & Delaney, 1997). In so far as arousal, affect, and attention regulation are considered to be antecedents of self-regulation (Kopp, 1982;Ruff & Rothbart, 1996), problems in these areas would predict that cocaine-exposed toddlers have more social-emotional problems than their nonexposed counterparts at 2 years of age.…”
mentioning
confidence: 99%
“…Emerging evidence suggests that prenatal cocaine exposure leads to an altered neurotransmitter system, activity, or receptor formation for all three monoaminergic systems (62). In a single study of acute pain responses in cocaine-exposed infants, Roumell et al (63) reported fewer discrete negative expressions of distress and anger and more sadness at 18 mo of age. Although this study did not control for maternal-infant interaction or the effects of the care-giving environment, and therefore may not reflect the direct effects of drug exposure per se, it might provide indirect evidence that altered prenatal 5HT levels are associated with subsequently altered pain reactivity.…”
mentioning
confidence: 99%